A Life-Course Study on Effects of Parental Markers of Morbidity and Mortality on Offspring’s Suicide Attempt - Mittendorfer-Rutz, Ellenor (Public Library of Science, 2012)
BACKGROUND: Research on the temporal relationship of parental risk factors with offspring’s suicide attempt is scarce and a life course approach has not been applied to date. We investigated the temporal relationship of parental morbidity and mortality with offspring’s suicide attempt and whether any such association was modified by offspring’s age at attempt. METHODS: We designed a case-control study through linkage of Swedish registers. Cases comprised all individuals in Sweden born 1973–1983 with inpatient care due to suicide attempt (15–31 years of age) and with information on both biological parents (N = 15 193). Ten controls were matched to each case (National Patient register with national complete coverage). Conditional logistic and spline regressions were applied. RESULTS: Particularly for women, most parental markers showed the strongest effect sizes if exposure was short-term (within 2 years after exposure) and related to the mother. Especially short-term exposure to maternal inpatient care due to psychiatric diagnoses had a significantly stronger effect on suicide attempt risk in women compared to men. Regarding exposure to parental inpatient care due to psychiatric diagnoses, short-term as opposed to long-term (exceeding 2 years after exposure) effects were highest during adolescence and decreased significantly with age for female and male offspring, respectively. CONCLUSIONS: Although limited by the fact that data on parental morbidity and the outcome of suicidality were based on in-patient data only, the data suggest that the high risks of suicide attempt in case of exposure to parental psychopathology and suicidal behavior particularly during adolescence and the strong short-term effects associated with maternal psychopathology for female offspring are of direct clinical importance.